Hubungan Kerapatan Mangrove dengan Kelimpahan Gastropoda di Teluk Gilimanuk, Bali - Valenciana, Rossa Lina; Surya Indrawan, Gede; Pratama Atmaja, Putu Satya (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025, 2025)
Mangrove ecosystems are located in coastal areas with high productivity due to the decomposition of litter decomposed by gastropods so that there is detritus, which is a source of energy for biota living in the waters. This study was conducted to determine mangrove density and gastropod abundance and the relationship between mangrove density and gastropod abundance in Gilimanuk Bay. Data collection methods and determination of sampling points were carried out using purposive sampling. Mangrove data were collected using a 10x10 m transect with 27 plots. Gastropod data collection was carried out using 1x1 m transects totaling 5 on each mangrove transect at each corner and center of the mangrove transect. Environmental parameters taken were temperature, pH, salinity, and DO. In Gilimanuk Bay, there are 13 types of mangroves from 7 different families. Mangrove density in Gilimanuk Bay amounted to 1944 - 2300 ind/ha, which is classified as very dense (good). The highest gastropod abundance value at station 1 was 16 ind/m 2, and the lowest was at station 3 at 3 ind/m 2 . Pearson correlation analysis showed a strong relationship between mangrove density and gastropod abundance.